If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x(6x + 2) = 88 Reorder the terms: 4x(2 + 6x) = 88 (2 * 4x + 6x * 4x) = 88 (8x + 24x2) = 88 Solving 8x + 24x2 = 88 Solving for variable 'x'. Reorder the terms: -88 + 8x + 24x2 = 88 + -88 Combine like terms: 88 + -88 = 0 -88 + 8x + 24x2 = 0 Factor out the Greatest Common Factor (GCF), '8'. 8(-11 + x + 3x2) = 0 Ignore the factor 8.Subproblem 1
Set the factor '(-11 + x + 3x2)' equal to zero and attempt to solve: Simplifying -11 + x + 3x2 = 0 Solving -11 + x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -3.666666667 + 0.3333333333x + x2 = 0 Move the constant term to the right: Add '3.666666667' to each side of the equation. -3.666666667 + 0.3333333333x + 3.666666667 + x2 = 0 + 3.666666667 Reorder the terms: -3.666666667 + 3.666666667 + 0.3333333333x + x2 = 0 + 3.666666667 Combine like terms: -3.666666667 + 3.666666667 = 0.000000000 0.000000000 + 0.3333333333x + x2 = 0 + 3.666666667 0.3333333333x + x2 = 0 + 3.666666667 Combine like terms: 0 + 3.666666667 = 3.666666667 0.3333333333x + x2 = 3.666666667 The x term is x. Take half its coefficient (0.5). Square it (0.25) and add it to both sides. Add '0.25' to each side of the equation. 0.3333333333x + 0.25 + x2 = 3.666666667 + 0.25 Reorder the terms: 0.25 + 0.3333333333x + x2 = 3.666666667 + 0.25 Combine like terms: 3.666666667 + 0.25 = 3.916666667 0.25 + 0.3333333333x + x2 = 3.916666667 Factor a perfect square on the left side: (x + 0.5)(x + 0.5) = 3.916666667 Calculate the square root of the right side: 1.979057015 Break this problem into two subproblems by setting (x + 0.5) equal to 1.979057015 and -1.979057015.Subproblem 1
x + 0.5 = 1.979057015 Simplifying x + 0.5 = 1.979057015 Reorder the terms: 0.5 + x = 1.979057015 Solving 0.5 + x = 1.979057015 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = 1.979057015 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = 1.979057015 + -0.5 x = 1.979057015 + -0.5 Combine like terms: 1.979057015 + -0.5 = 1.479057015 x = 1.479057015 Simplifying x = 1.479057015Subproblem 2
x + 0.5 = -1.979057015 Simplifying x + 0.5 = -1.979057015 Reorder the terms: 0.5 + x = -1.979057015 Solving 0.5 + x = -1.979057015 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.5' to each side of the equation. 0.5 + -0.5 + x = -1.979057015 + -0.5 Combine like terms: 0.5 + -0.5 = 0.0 0.0 + x = -1.979057015 + -0.5 x = -1.979057015 + -0.5 Combine like terms: -1.979057015 + -0.5 = -2.479057015 x = -2.479057015 Simplifying x = -2.479057015Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.479057015, -2.479057015}Solution
x = {1.479057015, -2.479057015}
| 120=4x*40 | | 4(p-8)=4+6p | | -14.8-k=14.3 | | D+27=-4 | | (1/3)*(121/900) | | 9u-3=27 | | (11/30)*(11/30) | | (x+375)(x+240)=130500 | | 2x-(3/x)=5 | | 4(49-x^2)=0 | | 11/30*11/30 | | 5(5c-10)-6c=3c+14 | | 164.25=9x | | c-61/2-11/4 | | -20=3+8(v-5) | | -2+3=5x-4 | | 1.4(4m+2)-2.2m= | | 16x^2/28x=0 | | y/19.2=6 | | 5x+1=x-4 | | 14=35m | | 6t^2-19t-7=0 | | -9(5d+7)=28+3d | | (8x+1)(x-8)=0 | | 34+4x-8+76-X=180 | | (x+375)(x+240)=x | | 3n-7=r-16 | | 11/2×?=6 | | 3(4a+2)+6a=9a-5 | | H=-b/2a | | 7c+15-5=73 | | 15/x=4/5 |